Factors That May Influence the Experience of Hot Flushes by Healthy Middle-Aged Women - Ziv-Gal, Ayelet (Mary Ann Liebert, Inc., 2010)
BACKGROUND: Interest in menopausal symptoms in general and hot flushes (HFs) in particular has grown in recent years. This is mostly due to increased awareness and the vast impact these symptoms have on women's lives. Despite the high prevalence of women who experience HFs, a definitive etiology for HFs is yet to be found. Our objective was to review the current literature dealing with associated factors for experiencing HFs and to provide a synthesized overview on this common and often debilitating condition. METHODS: We systematically searched the English-language literature in the PubMed database using relevant key words and included only those articles that contained information on associated factors for HFs in generally healthy midlife women. RESULTS: Both conflicting scientific results between studies documenting factors that influence HFs and the lack of validated measuring tools make it difficult to truly pinpoint associated factors for HFs. Nonetheless, we identified the following clusters of associated factors: the menopausal stages, sex steroid hormones, other endocrine agents, genetic polymorphisms, race/ethnicity, body mass index (BMI) and obesity, mood disorders, smoking, soy isoflavones and phytoestrogens, alcohol consumption, and physical activity. CONCLUSIONS: No single associated factor was consistently identified as having a major role in experiencing HFs. More resources should be directed to develop a unified study system along with multivariable analyses to get a better understanding of this condition, which often imposes a tremendous social and personal toll on the women who experience it.